Demystifying Classroom Assessment: Unleashing the Power of Technology Tools - Samuel Adenubi Onasanya; Abdu Danyaro; Justina Ojoma Attah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Background: Technology is a tool for instruction, not a replacement for teachers. Teachers are crucial for our nation's future and are essential implementers and integrators of technology in classrooms. They are responsible for innovative use of technology, as it enhances efficiency and effectiveness in everyday life. ICT comprehensively combines computer and telecommunication technology. Aim: They are also commonly used for the certification of competence, to monitor educational standards, and to provide learners with feedback. The qualitative aspect of assessment and evaluation in the field of education has a cutting-edge relationship with students’ academics. Method: Teachers no doubt are saddled with many responsibilities which range from writing lesson plans and notes to instructional delivery and assessment. Hence there is a need for teachers to span to the innovation technology is offering by embracing technological-based assessment. This paper explored the roles of technology in bridging the gap between the paper-pencil assessment to technology-enhanced assessment and proffered strategies on how these assessment apps can be used in the classroom. The study revealed that there are free assessment applications teachers can use to grade students, thereby reducing their workloads. It was therefore recommended among others that training and seminars should be organised for teachers to enlighten them on technology-based assessment. Result and Discussions: Teachers need to take cognizance of the relevancy of the technological tools. It was further pointed out that while observing the relevance of the technology resources, there should be congruence between the tech tools and instructional curriculum. Other factors to be considered are the; appropriateness of the content and alignment with the learning goals. Teachers need to have clear-cut goals before selecting any technology for assessment. Among the common goals to be considered are; efficiency, cost, end-user proficiency, collaboration, and capacity. Conclusıon: Assessment is vital to the education process. Online assessment can help learners engage more effectively and flexibly in knowledge and can help teachers manage assessment more proficiently and efficiently.